Border control: Anatomical origins of the thymus medulla. Issue 8 (August 2015) - Anderson, Graham; Jenkinson, William E.
<x xml:space="preserve">Abstract</x> The thymus is an anatomically compartmentalized primary lymphoid organ that fosters the production of self‐tolerant T cells. The thymic cortex provides a specialized microenvironment in which cortical thymic epithelial cells (cTECs) support the positive selection and further differentiation of self‐MHC‐restricted thymocytes. Following their migration into the medulla, positively selected thymocytes are further screened for self‐reactivity, which involves both negative selection and Foxp3+ regulatory T cell generation via interactions with medullary thymic epithelial cells (mTECs). Given the importance of both cortical and medullary microenvironments for T cell development, studies that address the developmental origins of cTECs and mTECs are important in understanding the processes that shape the developing T cell receptor repertoire, and reduce the frequency of self‐reactive T cells that initiate autoimmune disease. In this issue of the European Journal of Immunology, Onder et al. [Eur. J. Immunol. 2015. 45: 2218‐2231] identified a subset of podoplanin+ mTECs in mice that reside at the corticomedullary junction (CMJ), show that their development is important to establish self‐tolerance, and require the presence of self‐reactive T cells. Collectively, their findings highlight the CMJ as a potential repository for precursors of the mTEC lineage, and provide a better understanding of thymus medulla formation.